2016
DOI: 10.1590/s1806-37562015000000180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alpha-1 antitrypsin deficiency and allele frequency in patients with COPD in Brazil

Abstract: Objective:To determine the prevalence of alpha 1-antitrypsin (AAT) deficiency (AATD), as well as allele frequency, in COPD patients in Brazil. Methods:This was a cross-sectional study involving 926 COPD patients 40 years of age or older, from five Brazilian states. All patients underwent determination of AAT levels in dried blood spot (DBS) samples by nephelometry. Those with DBS AAT levels ≤ 2.64 mg/dL underwent determination of serum AAT levels. Those with serum AAT levels of < 113 mg/dL underwent genotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
4
11
0
11
Order By: Relevance
“…In inconclusive cases, SERPINA gene sequencing was performed. Among the patients evaluated by Russo et al, 9 the AAT values indicated the need for additional investigation in 9.2%, the serum AAT concentration was < 113 mg/dL in 2.6%, and the prevalence of the PI*Z allele was 0.8%, similar to that described in other countries 9 …”
supporting
confidence: 71%
See 1 more Smart Citation
“…In inconclusive cases, SERPINA gene sequencing was performed. Among the patients evaluated by Russo et al, 9 the AAT values indicated the need for additional investigation in 9.2%, the serum AAT concentration was < 113 mg/dL in 2.6%, and the prevalence of the PI*Z allele was 0.8%, similar to that described in other countries 9 …”
supporting
confidence: 71%
“…The data presented in the study conducted by Russo et al, 9 published in the current issue of the JBP, are unprecedented in that they show the prevalence of AATD in 926 COPD patients in five Brazilian states. The diagnosis of AATD was based on an AAT cut-off point of < 2.64 mg/dL in dried blood samples on filter paper.…”
mentioning
confidence: 97%
“…α 1 -AT is a glycoprotein protease inhibitor encoded by the SERPINA1 gene. SERPINA1 mutations lead to decreased α 1 -AT in lung tissue resulting in an increased risk of COPD emphysema [ 60 ]. α 1 -AT deficiency is a prototypical example for precision medicine in COPD as it has identifiably genetic underpinnings, with specific epidemiology and clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…We found a prevalence of 5.1% of A1ATD in our COPD outpatient clinic. In a recent study, Russo et al found that 2.8% of patients with COPD in Brazil had A1ATD, 2 which is an alarming finding considering the low frequency of this diagnosis in clinical practice and the small number of articles published on A1ATD in the Brazilian population. 2 , 15 Our country has a vast racial diversity, miscegenation and European immigration from countries where the frequency of alleles involved with A1ATD is high.…”
Section: Discussionmentioning
confidence: 99%
“… 1 ) The only Brazilian study reporting on the prevalence of A1ATD estimates that 2.8% of patients with chronic obstructive pulmonary disease (COPD) have this deficiency. 2 The Platino study showed that, in the city of São Paulo, 15.8% of individuals aged 40 years or older had COPD, 3 ) which indicates that there is probably a large number of patients with undiagnosed A1ATD.…”
Section: Introductionmentioning
confidence: 99%